Analysis of the Effectiveness of Combination of Manual Keyframes and Expressions in Creating Animations Using Adobe After Effects - Imam Ainudin Pirmansah; Muhammad Misbahul Munir (SMART : Jurnal Teknologi Informasi dan Komputer, 2024)
This study analyzes the effectiveness of the combination of manual keyframes and expressions in procedural animation using Adobe After Effects. The focus of the study includes processing time, animation quality, and efficiency of expression use by animators with different skill levels: beginners, intermediate, and professionals. The results showed that the use of expressions can reduce processing time by up to 20%, especially in the professional group, without reducing animation quality. ANOVA analysis revealed significant differences between groups based on efficiency and quality of results. The combination of manual keyframes and expressions proved effective in increasing efficiency and producing high-quality animations. This study contributes to multimedia education and animation practice, providing guidance for optimizing animation techniques.